The effect of temperature on physiology, toxicity and toxin content of the benthic dinoflagellate Coolia malayensis from a seasonal tropical region. (15th October 2020) - Li, Xin; Yan, Meng; Gu, Jiarui; Lam, Veronica T.T.; Wai, Tak-Cheung; Baker, David M.; Thompson, Philip D.; Yiu, Sam K.F.; Lam, Paul K.S.; Leung, Priscilla T.Y.
Highlights: Temperature affected the growth and toxicity of Coolia malayensis . Growth and abundance were optimized at 24°C. Higher Fv /Fm and total phaeo-pigments values were observed in log phase at 28°C. Toxicity of C. malayensis coincided with high water temperature. C. malayensis produced more lipophilic algal toxins at a high temperature. Abstract: Coolia malayensis is one of the commonly found benthic dinoflagellates in Hong Kong which can produce biotoxins and threaten the early life stages of marine invertebrates. Seawater temperature has been recognized as one of the primary environmental factors that affect the formation of harmful algal blooms. The present study evaluated the responses of C. malayensis, including growth, toxicity and toxin content (putative analogues of okadaic acid and azaspiracids), after exposure to a range of seven different temperatures ( i.e., 16°C, 18°C, 20°C, 22°C, 24°C, 26°C, and 28°C). The highest algal density and specific growth rate were recorded at 24°C. Significantly higher Fv /Fm (maximum quantum yield of PSII) and total phaeo-pigment values were observed in the exponential growth phase at 28°C. The toxicity of the algal extract, which was assessed by the lethality rate of Artemia larvae, increased with temperature. The highest toxin content was detected at the second highest temperature treatment, i.e., 26°C. Overall, temperature had significant effects on the physiological activities and toxicity of C. malayensis . This study has raised attention to the potentially increasing risks posed by toxic benthic dinoflagellates during heat waves in coastal waters. Graphical abstract: Image, graphical abstract